2000
DOI: 10.1073/pnas.97.11.5895
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the mammalian brain-specific, Mg 2+ -dependent neutral sphingomyelinase

Abstract: The enzymatic breakdown of sphingomyelin by sphingomyelinases is considered the major source of the second messenger ceramide. Studies on the contribution of the various described acidic and neutral sphingomyelinases to the signaling pool of ceramide have been hampered by the lack of molecular data on the neutral sphingomyelinases (nSMases). We recently identified a mammalian nSMase, an integral membrane protein with remote similarity to bacterial sphingomyelinases. However, its ubiquitous expression pattern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
285
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(305 citation statements)
references
References 34 publications
14
285
1
1
Order By: Relevance
“…The PS relocation also causes flipping of SM from outer to inner leaflet and hydrolysis by a cytosolic SMase (66)(67)(68) to generate ceramide with subsequent activation of death cascade mechanisms.…”
Section: Sm Sm Synthases and Smasesmentioning
confidence: 99%
“…The PS relocation also causes flipping of SM from outer to inner leaflet and hydrolysis by a cytosolic SMase (66)(67)(68) to generate ceramide with subsequent activation of death cascade mechanisms.…”
Section: Sm Sm Synthases and Smasesmentioning
confidence: 99%
“…Thus, the identification of PA/PS-interacting proteins as well as their binding domains is of interest, and the information will provide further insight into the lipid interaction and regulation of these effectors. Previous studies have shown that nSMase2 activity can be stimulated by APLs (6,31). However, as nSMase2 does not contain a previously characterized phospholipid binding domain, it is unclear if and where APLs interact with this enzyme.…”
mentioning
confidence: 99%
“…Recently, considerable progress has been made regarding the specific roles of the identified N-SMase isoforms, particularly neutral sphingomyelinase 2 (nSMase2), in signal transduction and a variety of cell processes (11). Mammalian nSMase2 was first identified in 2000 based on similarity to bacterial SMase (6). The human nSMase2 protein is a membrane-bound 655 amino acid protein consisting of a C-terminal catalytic domain, two N-terminal hydrophobic segments (HSs), and a 200-residue collagen-like domain between the N and C termini (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations